Spider mite control and resistance management: does a genome help?. Issue 2 (14th June 2012) - Van Leeuwen, Thomas; Dermauw, Wannes; Grbic, Miodrag; Tirry, Luc; Feyereisen, René
Abstract: The complete genome of the two‐spotted spider mite, Tetranychus urticae, has been reported. This is the first sequenced genome of a highly polyphagous and resistant agricultural pest. The question as to what the genome offers the community working on spider mite control is addressed. Copyright © 2012 Society of Chemical Industry